Implementing a Care Model for Bedridden Stroke Survivors: A Qualitative Study in Northeastern Thailand [Letter] - Zhang H; Liu J (Patient Preference and Adherence)
Haihang Zhang,1 Jiayang Liu2 1Guiyang Institute of Humanities and Technology, Guiyang, Guizhou, 550025, People’s Republic of China; 2Faculty of Educational Sciences and Technology, Universiti Teknologi Malaysia, Skudai, Johor, 81310, MalaysiaCorrespondence: Haihang Zhang, Email 2022966983@student.uitm.edu.my